Bioinformatic analysis and purification of Glutathione Transferase (GST) from Pseudomonas sp. UW4 - Kong, Christina Wen Hui; Tan, Irene Kit Ping; Zazali Alias, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study aimed at identifying and purifying cytosolic glutathione transferase isoforms expressed in Pseudomonas sp. UW4. Search at UniProt (https://www.uniprot.org/uniprot/), has indicated that there were 20 genes encoding putative glutathione transferases for the microorganism. The molecular weights of the isoforms ranged from 17.6 to 34.06 kDa. SDS-polyacrylamide gel electrophoresis revealed that the GST purified using Sulfobromophthalein-glutathione (BSP) affinity column, resolved into a single band with a low molecular weight (MW) of 16 kDa with the pI value of 6.0. Purified GST was reactive towards ethacrynic acid, 1-chloro-2,4-dinitrobenzene, cumene hydroxide, and hydrogen peroxide, but no detectable activity with Trans-2-octenal, hepta-2,4-dienal and Trans-4-phenyl-3-butene-2-one. This has proven that putative GST possessed peroxidase activity and proposed to be similar to PputUW4_00801 (putative glutathione S-transferase) of Pseudomonas sp. UW4 according to its estimated molecular weight and the pI values obtained experimentally.